2015
DOI: 10.1186/s40561-015-0015-x
|View full text |Cite
|
Sign up to set email alerts
|

The internet and education in the developing world - hopes and reality

Abstract: Information and communication technologies have made a major impact on education. This raises hopes in countries like India which are undergoing rapid growth in their educational efforts. Will Information and Communication Technologies create a revolution in the education sector? What can we expect in the way of impact due to the spread of access to the Internet? Will Internet access over the mobile phone make rapid advances possible in rural areas? What evidence is available to judge popular claims and predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 9 publications
0
18
0
2
Order By: Relevance
“…Internet connectivity, easy accessibility, and power interruptions are the common issues that we face often being in developing countries for virtual learning. [12,13] In our study too, though more respondents believe that the software used for online learning is user friendly but the internet connectivity is an important issue hindering the smooth conduction of class. A study conducted in Liberia for introducing e-learning solutions in medical education has also concluded that inadequate infrastructure, limited internet bandwidth, lack of skilled staffs, and unreliable electricity supply are the major hindrances in the resource-limited settings for virtual learning.…”
Section: Discussionmentioning
confidence: 65%
“…Internet connectivity, easy accessibility, and power interruptions are the common issues that we face often being in developing countries for virtual learning. [12,13] In our study too, though more respondents believe that the software used for online learning is user friendly but the internet connectivity is an important issue hindering the smooth conduction of class. A study conducted in Liberia for introducing e-learning solutions in medical education has also concluded that inadequate infrastructure, limited internet bandwidth, lack of skilled staffs, and unreliable electricity supply are the major hindrances in the resource-limited settings for virtual learning.…”
Section: Discussionmentioning
confidence: 65%
“…In the developing countries, access to technology may not be affordable to all and 80% students may remain deprived of computers and internet and the need for cheap, rugged equipment for the rural students in the developing countries persists. 15 In a Nigerian study by Jibrin MA et al reported that challenges faced in the use of internet were its speed as well as deficient stable power supply and recommended support by government for tertiary institutions. 16 In Pakistan the government has ordered a 20% cut in school fees, 17 amid lockdowns affecting the lower and middle class sadly the educational sector remains grossly neglected in terms of state sponsorship.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Industrial Revolution 4.0 (IR 4.0) and Internet of Things (IoT) emphasise on internet and automation technology becoming a norm in daily human life. [1][2][3] Many traditional and manual technological approaches have become obsolete and archaic and are no longer relevant. As technology has become an integral part of human life, its significance is even more so apparent Strengths and limitations of this study ► In light of the global COVID-19 pandemic, it is important to assess the effectiveness of technologybased learning in comparison with traditional teaching among undergraduate healthcare students.…”
Section: Introductionmentioning
confidence: 99%